PERKAWINAN DI BAWAH UMUR: POTRET BURAM ANAK PEREMPUAN DI CIANJUR - Nur Rofiah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
This paper studies marriages involving minors in Cianjur. The study was carried out in 2012, with a specific focus on women. Data was collected through in-depth interviews, observations in the field, Focused Group Discussions, and a review of the literature. This study finds that even after the enactment of Law No. 1 Year of 1974 on Marriage—which established a minimum age of marriage for brides—the practice of marriage with minors is still prevalent, especially in Cianjur. While the actual number of marriages involving minors is difficult to determine—these marriages are performed by religious leaders (ajengan) and are not officially registered—this study finds that some women married at the age of 7. Underaged marriage has complex causes and effects, such as legal factors (state), sociocultural factors (society), and factors of religious interpretation (religious leaders). Adverse effects of marriage involving female minors are widely experienced, such as sexual intercourse before menstruation, and a continuous cycle of pregnancy, childbirth, and breastfeeding. All of those have adverse effects on the physical condition of women and also means that these women do not develop to their full potential. The study recommends raising social awareness about the need to register marriages with the Office of Religious Affairs as well as to tighten checks for compliance with the administrative requirements of marriage.